Adorning and Adoring: The Sacred Trees of India - Fowler-Smith, Louise (Journal for the Study of Religion, Nature and Culture, 2018)
Sacred trees are found throughout India and venerated by those of varied religious groups, including animists, devotees of local cults, Hindus, Buddhists, and Jains. Since 2003 I have travelled the sub-continent of India, conducting interviews and photographing the aesthetic enhancement of trees as an act of worship. Here, examples of veneration and a selection of the myths, beliefs, and rituals that underlie this practice are provided. These trees, through their adornment by worshippers, become subjects of adoration for not only Indians, but also for outsiders as well. In reflecting on this, the link between the aesthetic and the sacred is shown to have the potential to inspire ethical, eco-conscious, and transcultural responses to the natural world.